Improving subnational government development finance in emerging and developing economies: Toward a strategic approach - Paul J. Smoke (Asian Development Bank Institute (ADBI), 2019)
Considerable attention has been given to enhancing subnational development finance in response to the 2008 global financial crisis and recent global development agendas, including the Sustainable Development Goals, Financing for Development, and Habitat III/New Urban Agenda. Much work on this topic is fragmented, focusing on specific elements of development finance: fiscal transfers, capital market access, public-sector lending agencies, or public-private partnerships. Most countries, however, have a range of subnational governments with varying needs and capacities that require different and evolving mixes of development finance mechanisms. Enabling greater subnational borrowing is often desirable but requires adoption of other reform policies to improve the fiscal capacity and creditworthiness of subnational governments over time. This paper reviews the rationale and potential for improving subnational development finance, outlines the overall landscape of institutional arrangements available for this purpose, and considers broad challenges involved. Based on a review of global practice and experience in selected Asian developing countries with a range of special entities and innovations to enhance subnational investment, it proposes a more integrated, strategic approach to building subnational development finance.
Keywords: H70; H71; H72; H74; H77; 330; Subnational government finance; intergovernmental transfers; subnational government debt; subnational government financial intermediaries; Asia